Civic and political e-participation of young immigrants - Malafaia, C.; Fernandes-Jesus, M.; Norberto R.; Neves, T.; Coimbra, L. J.; Menezes, I. (International Journal of E-Politics, 2013)
The internet is considered as an important forum to empower and engage groups outside the traditional political systems. However, the ‘digital divide’ might imply several disparities and even reinforce exclusion of those with low economic and cultural capital. This article intends to question how democratic and inclusive this virtual public sphere is and in which terms the new dynamics in contemporary societies encourage mobility by excluded groups. Through quantitative methodology, we sought to analyse the differences between migrant (Angolans and Brazilians) and non-migrant groups in Portugal, as well as the e-participation forms adopted by them and the factors that could predict such participation. This is essential towards a wider knowledge about this field, strengthening the understanding concerning the ambivalence about the potential of the internet as a space for the inclusion of groups at risk of exclusion from participation and, consequently from real citizenship.